دور شبكات التواصل الاجتماعي في ترويج السياحة الصحراوية دراسة حالة- وكالة غروب سوف - نريمان عبداللاوي; رحمة قانة; فهيمة بوخلخال (university of eloued جامعة الوادي, 2025)
" تهدف الدراسة إلى معرفة دور شبكات التواصل الاجتماعي في الترويج للسياحة الصحراوية في الجزائر عامة وولاية الـوادي خاصة، وذلك من خلال دراسة حالة وكالة غروب سوف. وتم الاعتماد على المنهج الوصفي التحليلي في الجانب النظري، ومنهج دراسة الحالة في الجانب التطبيقي من خلال استخدام أدوات المقابلة والملاحظة و الوثائق وهذا بالتواصل مع مسؤولي الوكالة. ووفقا لما تقدم خلصت الدراسة إلى مجموعة من النتائج أهمها: • الاستراتيجيات التــي تعتمدها وكالة غروب سوف في الترويج للسياحة الصحراوية هي التسويق بالمحتوى والإعلانات المجانية والمدفوعة والتسويق بالمؤثرين والتسويق بتجارب الزبائن؛ • وكالة غروب سوف تستغل شبكات التواصل الاجتماعي بنسبة عالية أحسن استغلال للترويج للسياحة الصحراوية؛ • المحتوى الذي تقدمه وكالة غروب سوف عبر شبكات التواصل الاجتماعي سمعي بصري وكتابي. توصي الدراسة بتعزيز التعاون بين مختلف الوكالات السياحية، والاستثمار في المجال السياحي، مع نشر الوعي بأهمية السياحة الصحراوية، حيث يعد الاعتماد على الترويج للسياحة الصحراوية عبر وسائل التواصل الاجتماعي خيارًا استراتيجيًا لا غنى عنه لتحقيق تنمية سياحية مستدامة في المناطق الصحراوية. "The study aims to explore the role of social media networks in promotion, specifically their role in promoting desert tourism in Algeria in general and the Wilaya of El oued (specifically ""Ghorob Souf"" travel agency) through a case study of ""Ghorob Souf"" travel agency. The research relied on a descriptive-analytical approach for the theoretical framework and a case study methodology for the applied aspect, using tools such as interviews, observation, and documents in communication with the agency’s officials. Based on this, the study concluded the following key results: -The strategies adopted by ""Ghorob Souf"" travel agency to promote desert tourism include: content marketing, free and paid advertisements, influencer marketing, and customer experience marketing. -""Ghorob Souf"" travel agency utilizes social media networks very effectively to promote desert tourism. -The content provided by the agency on social media platforms is audiovisual (video/audio) and written (text-based). The study recommends: enhancing cooperation among various tourism agencies, investing in the tourism sector, raising awareness about the importance of desert tourism, and relying on social media promotion as an indispensable strategic choice to achieve sustainable tourism development in desert regions.
ماستر
Keywords: شبكات التواصل الاجتماعي; سياحة صحراوية،; ترويج سياحي; وكالة غروب سوف; Social media networks; desert tourism; promotion; tourism promotion; "Ghorob Souf" travel agency.